Development of the analyser module for the MIDAS Data Acquisition System operating on the K600 magnetic spectrometer at iThemba LABS, Cape Town - Jones, Stephen David (Department of Physics, 2024)
The focal-plane detector package at iThemba LABS, Cape Town, is reviewed and a new analyser module is developed. The mathematical methods employed by the analyser are also reviewed and the final system is calibrated and tested against experimental data taken at iThemba LABS, Cape Town.